INDUSTRY-SPECIFIC APPLICATIONS OF IAM AND INFRASTRUCTURE IN CLOUD SECURITY - Kiran Kumar Suram (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article presents the dynamic evolution of Identity and Access Management (IAM) and cloud infrastructure security across diverse industry sectors. The article illuminates how organizations tackle complex security challenges through tailored IAM implementations while ensuring strict regulatory adherence. Examining healthcare's patient data protection requirements, financial services' transaction security demands, and retail's customer identity safeguards reveals each sector's distinctive security approaches. The content showcases how advanced IAM solutions transform organizational security frameworks through AI-driven controls, automated access management, and real-time threat detection. Furthermore, it encompasses industry-wide best practices, detailed implementation strategies, and the integration of modern security paradigms, including zero-trust architecture and DevSecOps methodologies. Special attention is given to cloud-specific security considerations, highlighting how multi-cloud environments and distributed systems reshape identity governance. The article demonstrates how organizations leverage cutting-edge technologies to strengthen their security posture while maintaining operational efficiency and user experience across various business contexts.